The Impact of Vitamin D Levels on Inflammatory Status: A Systematic Review of Immune Cell Studies - Calton, Emily K.; Keane, Kevin N.; Newsholme, Philip; Soares, Mario J. (PLOS ONE, 2015)
Chronic low-grade inflammation accompanies obesity and its related chronic conditions. Both peripheral blood mononuclear cells (PBMCs) and cell lines have been used to study whether vitamin D has immune modulating effects; however, to date a detailed systematic review describing the published evidence has not been completed. We therefore conducted a systematic review on the effect of vitamin D on the protein expression and secretion of inflammatory markers by human-derived immune cells. The review was registered at the International Prospective Register for Systematic Reviews (PROSPERO, Registration number CRD42015023222). A literature search was conducted using Pubmed, Science Direct, Scopus, Web of Science and Medline. The search strategy used the following search terms: Vitamin D or cholecalciferol or 1,25-dihydroxyvitamin or 25-hydroxy-Vitamin D and Inflam* or cytokine* and supplement* or cell*. These terms were searched in the abstract, title and keywords. Inclusion criteria for study selection consisted of human-derived immune cell lines or cellular studies where PBMCs were obtained from humans, reported in the English language, and within the time period of 2000 to 2015. The selection protocol was mapped according to PRISMA guidelines. Twenty three studies (7 cell line and 16 PBMCs studies) met our criteria. All studies selected except one used the active metabolite 1,25(OH)2, with one study using cholecalciferol and two studies also using 25(OH)D. Four out of seven cell line studies showed an anti-inflammatory effect where suppression of key markers such as macrophage chemotactic protein 1, interleukin 6 and interleukin 8 were observed. Fourteen of sixteen PBMC studies also showed a similar anti-inflammatory effect based on common inflammatory endpoints. Mechanisms for such effects included decreased protein expression of toll-like receptor-2 and toll-like receptor-4; lower levels of phosphorylated p38 and p42/42; reduced expression of phosphorylated signal transducer and activator of transcription 5 and decreased reactive oxygen species. This review demonstrates that an anti-inflammatory effect of vitamin D is a consistent observation in studies of cell lines and human derived PBMCs.